2017
DOI: 10.1111/medu.13482
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about coaching in medical education? A literature review

Abstract: There is weak- to medium-strength evidence to support coaching as a method of improving doctor well-being and enhancing non-technical skills, although the evidence base is limited as a whole. This review identifies strong evidence to support coaching as a method to improve technical skills. There is great scope for further studies investigating the power of coaching in medical students and doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
168
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 56 publications
0
168
0
7
Order By: Relevance
“…To date, coaching has been particularly effective in improving technical skills . There is also evidence that coaching supports non‐technical skills and improves physician well‐being . This study focuses on the skills supervisors need to effectively coach residents in medical education settings.…”
Section: Introductionmentioning
confidence: 99%
“…To date, coaching has been particularly effective in improving technical skills . There is also evidence that coaching supports non‐technical skills and improves physician well‐being . This study focuses on the skills supervisors need to effectively coach residents in medical education settings.…”
Section: Introductionmentioning
confidence: 99%
“…Coaching's surging popularity in medical education may be grounded, in part, in the extent to which it just seems to make intuitive sense. Spurred on by comparisons to the worlds of sports, music and executive coaching, medical educators have begun embracing the idea that coaching may effectively foster learning. Coaching has been touted as a necessary facilitator of competency‐based medical education approaches and, perhaps, as a necessary counterweight to the frequent assessments that such approaches require .…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations of the impact of coaching in surgical education have yielded promising results, with coaching interventions demonstrating improvements in both technical and non‐technical skills . Lovell's recent review of coaching in medical education revealed good quality data showing that coaching improves technical skills acquisition, reduces surgical error, improves examination scores and identifies struggling students . But as published work explores what coaching does , it has not tended to illuminate what coaching is in medical education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Watling and Ginsburg write about learners, I suspect many faculty members feel similarly about assessment. In response, coaching, which has long been utilised in business and sport to help individuals achieve their personal best, is emerging as an increasingly appreciated resource in the medical educator's toolbox . Shifting into a coaching mindset may not only lessen confusion with the terms used in everyday assessment conversations, but may also lead to a qualitative shift in the perceived tensions associated with formative activities by removing the assessment component from interactions intended to be purely developmental …”
mentioning
confidence: 99%